THE TRANSFORMATION OF MEDICAL RESEARCH DUE TO AND BEYOND THE COVID-19 PANDEMIC - Dewi, Kristin Purnama (Berkala Ilmiah Kedokteran Duta Wacana, 2024)
The COVID-19 pandemic has significantly altered various sectors, and the scientific community is no exception. It has reshaped the research landscape across numerous disciplines, profoundly impacting how medical research is conducted, prioritized, and funded. As we move into the post-pandemic world, understanding these transformations is crucial for evaluating shifts in medical research and contemplating their implications for future scientific inquiry. This editorial focuses on the pandemic-driven transformations in medical research, including methodological innovations, changes in research focus, and their implications for future research directions. The need to respond rapidly to a rapidly changing environment has accelerated the adoption of digital technologies and remote research methodologies. During lockdowns and periods of social distancing, the continuation of research increasingly relied on virtual collaboration and online data collection. This shift has highlighted how digital technologies can enhance research efficiency and brought attention to the necessity of robust frameworks to address the challenges associated with virtual interactions and remote data collection.